A Longitudinal Study of Relationships Between Vocational Graduates' Career Adaptability, Career Decision-Making Self-Efficacy, Vocational Identity Clarity, and Life Satisfaction. (February 2023) - Kvasková, Lucia; Hlado, Petr; Palíšek, Petr; Šašinka, Václav; Hirschi, Andreas; Ježek, Stanislav; Macek, Petr
Career construction theory proposes that high career adaptability leads to positive adaptation outcomes during career transition. However, the specific pathways of how this happens remain underexplored. Drawing on the career construction model of adaptation, we hypothesized that career decision-making self-efficacy mediates the link of career adaptability with vocational identity clarity and life satisfaction as two measures of adaptation outcomes. We conducted a three-wave survey with an initial sample of 3126 Czech upper-secondary vocational graduates transitioning from vocational school to the labor market. Structural equation modeling revealed that career decision-making self-efficacy fully mediated the relationship between career adaptability before graduation and vocational identity clarity 20 months later. In contrast, the mediation effect of career decision-making self-efficacy on the relationship between career adaptability and life satisfaction was not supported. Additionally, in contrast to the previous literature, career adaptability was not directly related to vocational identity clarity and life satisfaction. Nevertheless, our findings demonstrated a positive long-term association of career adaptability with adaptation outcomes within the working life domain. Practical implications and future directions are discussed.